2010
DOI: 10.1088/0953-2048/23/2/025028
|View full text |Cite
|
Sign up to set email alerts
|

Transport AC loss characteristics of a nine strand YBCO Roebel cable

Abstract: Transport AC loss in a short length of 9/2 YBCO Roebel cable (nine 2 mm wide strands) is measured. The AC loss data are compared with those in a 5/2 YBCO Roebel cable (five 2 mm wide strands) as well as that in a single strand. All the strands composing the cables and the single strand are insulated and cut from the same stock material. The validity of the measurement method was reconfirmed by results at a range of frequencies. At a wide range of I t /I c , the normalized AC losses in the Roebel cable were aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…The model also showed that by correctly transposing the strands, the average loss in each strand was reduced to a factor of 2.5 times that for a single stand. Similar experimental and simulation results have been observed in YBCO Roebel cables [13,14].…”
Section: Modelling and Simulationsupporting
confidence: 86%
“…The model also showed that by correctly transposing the strands, the average loss in each strand was reduced to a factor of 2.5 times that for a single stand. Similar experimental and simulation results have been observed in YBCO Roebel cables [13,14].…”
Section: Modelling and Simulationsupporting
confidence: 86%
“…Hence, each strand occupies all different locations of the double stack configuration. Therefore, all strands are electrically equivalent and should carry the same current and they should also have same transport ac loss [2,3]. In order to implement the constraint of equal current in the strands of Roebel cable, the current in the central strands is not allowed to exceed the current in the surface strands.…”
Section: Magnetic Field and Current Distributionmentioning
confidence: 99%
“…For HTS applications the current capacity of given wire at different temperatures and fields, I c (B, T, H), is usually scaled from 77 K, self-field, values. For HTS Roebel cable, composed of multiple strands of conductor, the 77 K critical current is strongly affected by the self-field [3][4][5]. To design devices using Roebel cable it is useful to understand the effect of self-field on the 77 K measurement in some detail.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, they may not be representative for the present nano-engineered material [16,17,18]. For Roebel cables there are also measurements for perpendicular applied fields [20,33,7,27], parallel ones [34] and transport currents [20,35].In this article, we simulate and discuss the AC loss due to an applied magnetic field at an arbitrary angle with the cable and we take into account a…”
mentioning
confidence: 99%